(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2021)
The design-based research (DBR) methodology has been standing out in the field of educational research promising to adapt to different scenarios and boost the development of educational innovations. However, 17 years after the beginning of the use of this methodology, there are still doubts about its potentiality. Given this, it is necessary to ascertain in which contexts this methodology has been used and what are the educational advances related to it. Thus, bibliometric mapping was carried out in this paper to generate indicators of studies on DBR, to indicate its relationship with the field of Science Education and situate Brazilian production in the international context. The study identified the distribution of publications by year, according to the number of publications, the main journals where these articles were published, the authors nationality, the most cited articles, the main keywords, and the network collaboration between authors. Data showed that the last five years have been the most promising for DBR publications and the North Americans were those who published more about this methodology. Despite the growing number of publications, the field of Science Education still makes little use of this methodology. The main applications found in DBR were related to teacher education, student motivation, and the use of information and communication technologies on teaching and learning.